159k views
2 votes
Find and simplify the expression if f(x)= x² - 5.f(8) + f(h) =

User Sierrodc
by
5.8k points

1 Answer

2 votes

Answer:

h²+54

Step-by-step explanation:

Given f(x) defined below:


f\mleft(x\mright)=x^2-5

Substitute h for x to find f(h):


f(h)=h^2-5

Similarly, substitute 8 for x to find f(8):


\begin{gathered} f(8)=8^2-5 \\ =64-5 \\ =59 \end{gathered}

Therefore:


\begin{gathered} f\mleft(8\mright)+f\mleft(h\mright)=59+(h^2-5) \\ =h^2+59-5 \\ =h^2+54 \end{gathered}

User Anatoliy Nikolaev
by
5.8k points